Correction: Utilizing the bioorthogonal base-pairing system of l-DNA to design ideal DNA nanocarriers for enhanced delivery of nucleic acid cargos. Issue 3 (16th March 2015) - Kim, Kyoung-Ran; Lee, Taemin; Kim, Byeong-Su; Ahn, Dae-Ro
<x xml:space="preserve">Abstract</x> Correction for 'Utilizing the bioorthogonal base-pairing system of l-DNA to design ideal DNA nanocarriers for enhanced delivery of nucleic acid cargos' by Kyoung-Ran Kim et al., Chem. Sci., 2014, 5, 1533–1537.